Pengaruh Pemberian Pupuk Dolomit dan Pupuk Kandang Sapi terhadap Sifat Kimia Tanah, Pertumbuhan dan Hasil Tanaman Kacang Hijau (Vigna radiata L.) di Distritu Baucau Timor Leste - RIBEIRO, DECIO ARISTA ESTANISLAU DA COSTA; KARTINI, NI LUH; WIJANA, GEDE (Agrotrop : Journal on Agriculture Science; Vol 7 No 1 (2017), 2017)
The Effect of Dolomit Fertilizer and Caw Manure on Soil Chamical Properties, Growth and Yield of Green Beans (Vigna radiata L.) in Distirct Baucau East Timor. Dry land use in East Timor Baucau District in particular is one step in improving the potential of land for the development of dry land crops such as green beans. The use of green bean varieties of finches and dolomite fertilizer and cow manure with multiple doses of use to be one of the alternative chemical properties of soil fertility improvement and increase crop yields of green beans. Fields trials have done to research the influence of dose and dose dolomite manure on soil chemical properties and yield of green beans on dry land in the Baucau District which lasts from January 2016 until March 2016. The experiment was arranged in the randomized block design with three replications. Treatment consist of a dose of fertilizer dolomite (0, 160, 320, 480 kgha-1) as the first factor and a dose of cow manure (0, 10, 20, 30 tha-1) as the second factor. The result showed that the interaction of dolomite fertilizer dose and dose cow manure affect the chemical properties of soil and yield of green beans. Increasing doses of fertilizer dolomite 480 kg ha-1 and 320 kg ha-1 affect the improvement of soil chemical properties of C-organic,P-avalaible, K-avalaible and Ca ground. Dose of cow manure 30 t ha-1 and 20 t ha-1 C-organic soil and crops yield in the form of dry weight of drying grain crops. Interaction dolomite fertilizer and cow manure can improve chemical properties (N-total and pH soil) may increase result of green beans (number of pods, fresh weight, dry weight oven plant, dry weight oven dried beans and heavy landscaping oven 100 seeds). Giving dolomite fertilizer with a dose of 480 kg ha-1 and cow manure 30 kg ha-1 can apllied to land in the study site and presence of advanced research different dosed to get best dosage with different plant species.